Effect of Nordic Walking training on iron metabolism in elderly women - Kortas J (Dove Medical Press, 2015)
Jakub Kortas,1 Katarzyna Prusik,2 Damian Flis,3 Krzysztof Prusik,1 Ewa Ziemann,4 Neil Leaver,5 Jedrzej Antosiewicz6 1Department of Recreation and Tourism, Gdansk University of Physical Education and Sport, Gdansk, Poland; 2Department of Biomedical Basis of Health, Gdansk University of Physical Education and Sport, Gdansk, Poland; 3Department of Bioenergetics and Physiology of Exercise, Medical University of Gdansk, Gdansk, Poland; 4Department of Physiology and Pharmacology, Gdansk University of Physical Education and Sport, Gdansk, Poland; 5The Immunosuppression monitoring service (IMS) Laboratory, Royal Brompton & Harefield NHS Foundation Trust, Heart Science Centre, Harefield Hospital, Harefield, UK; 6Department of Biochemistry, Gdansk University of Physical Education and Sport, Gdansk, Poland Background: Despite several, well-documented pro-healthy effects of regular physical training, its influence on body iron stores in elderly people remains unknown. At the same time, body iron accumulation is associated with high risk of different morbidities.Purpose: We hypothesized that Nordic Walking training would result in pro-healthy changes in an elderly group of subjects by reducing body iron stores via shifts in iron metabolism-regulating proteins.Methods: Thirty-seven women aged 67.7±5.3 years participated in this study. They underwent 32 weeks of training, 1-hour sessions three times a week, between October 2012 and May 2013. Fitness level, blood morphology, CRP, vitamin D, ferritin, hepcidin, and soluble Hjv were assessed before and after the training.Results: The training program caused a significant decrease in ferritin, which serves as a good marker of body iron stores. Simultaneously, the physical cardiorespiratory fitness had improved. Furthermore, blood hepcidin was positively correlated with the ferritin concentration after the training. The concentration of blood CRP dropped, but the change was nonsignificant. The applied training resulted in a blood Hjv increase, which was inversely correlated with the vitamin D concentration.Conclusion: Overall the Nordic Walking training applied in elderly people significantly reduced blood ferritin concentration, which explains the observed decrease in body iron stores. Keywords: ferritin, hemojuvelin, hepcidin, vitamin D, anti-agingA Letter to the Editor has been recieved and published for this article.